La pandemia COVID-19 y los Objetivos de Desarrollo Sostenible. Estrategias para la reconversión de los destinos turísticos de masas españoles - Ariadna Gabarda-Mallorquí; Rosa Maria Fraguell (Bollettino della Società Geografica Italiana)
The recent COVID-19 pandemic has put the mass tourism sector in Spain in check. The measures to contain the spread of the virus have led to the loss of millions of euros and thousands of jobs in the sector. There are three factors regarding mass tourism management that make the sector even more fragile, jeopardizing its recovery once the pandemic is under control: currently, tourist destinations cannot yet guarantee physical distance, their work structure is not inclusive, and there are not enough multi-sector global alliances. These three circumstances do not allow the sector to be more resilient and able to face future outbreaks. The United Nations Sustainable Development Goals are, today more than ever, essential for the adaptation of the sector to new post-COVID-19 phases. Thus, with a strategy based on objectives 3, 8 and 17, the sector will move towards healthier, more inclusive and more cooperative tourist destinations, being able to face new outbreaks and even future health crises.